Guidelines for modelling reactive systems with coloured Petri nets - Madalena, Gonçalves (2013)
This paper focus on the modelling of reactive systems, more particularly, control systems. A set of guidelines is proposed in order to build models that support analysis, simulation and prototyping. The guidelines are split in two parts; the analysis of a problem is addressed first, followed by the design with Coloured Petri Nets (CPNs). A smart library example is used as case study. The models developed under this approach turn out to be modular, parameterisable, configurable and executable.